Synthesis of Gelatin-Free Halal Capsule Shells Based on Microcrystalline Cellulose from Solid Sugar Palm (Aren) Waste - Pradaniz, Erika Putri; Prawesti, Widya Ayu; Iwahyuningtyas, Intan; Naufiannida, Nasywa Alya; Maharani, Anggistia; Fadilah, Fadilah (Equilibrium Journal of Chemical Engineering, 2025)
ABSTRACT. Capsules are one of the most used drug delivery media. Capsule shells are made from gelatin, a protein derived from hydrolyzed collagen, which is extracted from animal skin, tissue, and bones. Gelatin from animals is susceptible to contamination with pathogens. Alternative ingredients that are safe to use include those derived from vegetables, such as palm starch dregs. The cellulose content in solid sugar palm waste is quite high, so it has potential for use in making capsule shells. However, cellulose does not dissolve easily in water. Improving this property can be done by changing the size. Microcrystalline Cellulose (MCC) is obtained by acid hydrolysis of cellulose, resulting in the loss of the amorphous portion, leaving the crystalline portion. Its good dispersion in water makes MCC a matrix-forming agent when mixed with HPMC, a gelatin substitute. This research intends to examine the impact of involving MCC derived from solid sugar palm waste on the characteristics of the capsule shell. The properties include uniformity of weight, water content, ash content, pH, and solubility. The acid hydrolysis method is used in the synthesis of MCC. FTIR results show that MCC has the same functional groups as α-cellulose. SEM results show that although some parts are nano-sized, there are still other parts that are micron-sized. Capsule shells were made with varying concentrations of MCC 1%, 4%, 7%, and 10% with the addition of HPMC 2%, PEG-400 2%, and water. The results show that the best variation is at 4% MCC, which meets the standards of Farmakope Indonesia VI edition. On average, the capsule’s weight is 0.0938 grams, water content is 13.73%, ash content is 1.35%, pH 6, solubility in water is 19 minutes 49 seconds, and solubility in acid is 2 minutes 40 seconds.Keywords:α-selulosa, Capsule shell, Microcrystalline celluloses, Drug delivery, Palm starch dregs.